Analysis Of Compressive Strength Of Foam Mortar With The Use Of Teratak Buluh Sand And Ringgit Sand - Tisnawan, Rahmat; Doni Rinaldi Basri; Puspa Ningrum; Zulfikar, Adyus (JIM - Journal International Multidisciplinary, 2023)
The core material in the manufacture of lightweight concrete (foam mortar) is influenced by the composition of the mixture of fine aggregate. The purpose of the study was to compare foam mortar with foaming agent using two types of fine aggregates from different sources, namely Teratak Buluh Sand, Kampar and Ringgit Sand, Indragiri Hulu. This study focuses on testing the properties of fine aggregate, flow value, bulk density and Unconfined Compression Strength (UCS) of foam mortar. The fine aggregate of Teratak Buluh has a mud content value of 0.50% while the ringgit sand silt content value is higher with a 1.92% mud content percentage value where the maximum silt content value is 3%. In this study, both types of aggregates had variations in the mixture of sand to cement, namely 18/82%; 16/84%; 15/85%; 14/86% and 12/88%. The flow value in a mixture of 14/86% Teratak Buluh Sand and a mixture of 12/88% ringgit sand has a flow value of 19.00 cm which is the highest value of the five variations. Teratak Buluh sand mixture of 14/86% has a higher value than the five variations, which is 781.67 Kg/m3 while ringgit sand has the highest density value of 758.12 Kg/m3 in a mixture of 12/88%. The value of Unconfined Compression Strength (UCS) using Teratak Buluh sand is superior when compared to the use of ringgit sand. The average value of the Unconfined Compression Strength (UCS) of lightweight foam mortar material from the use of mixed teratak buluh sand of 14/86% (1136.80 kPa) and 12/88% (1175.78 kPa) has the highest value which is close to the reference Unconfined Compression Strength (UCS) of the mixture. 15/85% (1253.73 kPa) while the mixture was 18/82%; 16/84% Teratak Buluh and 18/82%; 16/84%; 15/85%; 14/86%; 12/88% ringgit sand has the lowest f Unconfined Compression Strength (UCS) which does not meet the design Unconfined Compression Strength (UCS) of 1000 kPa and 800 kPa based on the SE-PUPR-46-SE-M-2015 specifications.